Changes in the Mechanical Properties of the Horizontal Force-Velocity Profile During a Repeated Sprint Test in Professional Soccer Players - Aedo-Munoz, E (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The objective was to analyze the changes in the horizontal force-velocity profile (HFVP) during the execution of repeated sprinting. Methods: Seventeen first-division Chilean soccer players completed a repeated sprint protocol consisting of eight sprints of 30 m with 25-s pauses between repetitions. The behavior of HFVP variables in each attempt was recorded from video recordings and analysis in the MySprint® application. Results: Differences (p < 0.05) were found between sprints in the following: time (T), starting from sprint 5 (F = 35.6; η2p = 0.69); theoretical maximum speed (V0), starting from sprint 4 (F = 29.3; η2p = 0.51); maximum power (PM), starting from sprint 5 (F = 17; η2p = 0.52); rate of decrease in force index produced at each step (DRF), starting from sprint 1 (F = 3.20; η2p = 0.17); and RF10, starting from sprint 1 (F = 15.5; η2p = 0.49). In comparison, F0 and RFpeak did not present any differences (p > 0.05). Conclusion: The HFVP variables more sensitive to the effects of fatigue induced by an RSA protocol are those associated with the production of force at high speeds, being V0, DRF, and Pmax, while those that contribute to the generation of force at the beginning of the sprint, F0 and RFpeak, do not present essential variations. © 2022 by the authors.